Réponses

Meilleure réponse !
2013-01-21T20:26:55+01:00

a) (x-2)(x+2) = 0

soit x-2 =0 alors x = 2

soit x+2 = 0, alors x = -2

 

b) x²+5x = 0

= x(x+5) = 0

soit x = 0

soit x+5 = 0 alors x = -5

 

c) (4x+3)² -1 = 0

= (4x+3-1)(4x+3+1) = (4x+2)(4x+4)

soit 4x+2 = 0 donc 4x = -2 et x = -2/4 ou -1/2

soit 4x+4 = 0 donc 4x = -4 et x = -1

 

(2x+5)²-x² = (2x+5-x)(2x+5+x) = (x+5)(3x+5)

soit x+5 = 0 donc x= -5

soit 3x+5 = 0 donc 3x =-5 d'où x = -5/3

 

d) 4x² -7x = 0

x(4x-7) = 0

soit x = 0

soit 4x-7 = 0, donc 4x =7 d'où x = 7/4